PERFORMANCE COMPARISON OF BLIND SOURCE SEPARATION ALGORITHMS BY INDEPENDENT COMPONENT ANALYSIS - KANADI (NIM: 13204209), MARKO
Blind Source Separation system is used for estimating source signals from the mixture signals. The system is used for separating wanted signals from the interferences and unwanted noise. The critical issue in BSS system is the determination of the score function whose form depends on the statistical distribution of the source signal. Old BSS algorithms were only able to separate limited kinds of signals since their score function were static. Since source signal can be any kind of signal, a score function which is flexible and shapeable regarding to the distribution of the source signal is desired.